The Jesus Sutras: Rediscovering the lost religion of Taoist Christianity. Martin Palmer. - Hunter, Erica C.D. (Buddhist Studies Review, 2003)
The Jesus Sutras: Rediscovering the lost religion of Taoist Christianity. Martin Palmer. Piatkus, London 2001. xvi, 270 pp. £17.99. ISBN 0 7499 2250 8.